2012
DOI: 10.1597/10-167
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary Approach for Esthetic, Functional, and Quality-of-Life Outcome in Soft Palate Cleft Patient

Abstract: The fabrication of a Suersen obturator prosthesis with titanium framework is described in the case of a 43-year-old man with congenital absence of the soft palate. The patient revealed an open soft palate, bilateral cleft lip and palate, Angle Class III dental malocclusion, and anterior and posterior crossbite. He was treated with a multidisciplinary approach. A Dolder bar was fabricated between the maxillary canines, and telescopic crowns were prepared for maxillary premolars. Angle Class III tooth relation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Some authors suggested that the bulb works as a sensorimotor stimulator that helps muscle function, especially when associated with speech therapy [21,22]. This appliance also controls nasal emission during speech and prevents nasal regurgitation of food and fluids during swallowing [23].…”
Section: Introductionmentioning
confidence: 99%
“…Some authors suggested that the bulb works as a sensorimotor stimulator that helps muscle function, especially when associated with speech therapy [21,22]. This appliance also controls nasal emission during speech and prevents nasal regurgitation of food and fluids during swallowing [23].…”
Section: Introductionmentioning
confidence: 99%